Pengaruh Model Pembelajaran Project Based Learning (PjBL) berbantuan LKPD pada Materi IPA Sistem Ekskresi Manusia terhadap Kemampuan Berpikir Tingkat Tinggi Siswa Kelas VIII - Pramesthi, Galuh; Pratika, Vindhy Dian Indah (Universitas Nusantara PGRI Kediri, 2024)
This study aims to examine the effect of the Project Based Learning (PjBL) learning model assisted by Student Worksheets (LKPD) on higher order thinking skills (HOTS) and improving learning outcomes of class VIII students at SMPN 1 Gondang Tulungagung on the science material of the human excretory system. This study used a quasi-experimental design with Non-Equivalent Control Group Design, involving an experimental group that received PjBL treatment assisted by LKPD and a control group with conventional methods. The study sample consisted of 38 class VIII students selected by purposive sampling. The results showed that there was a significant difference between the average value of student learning outcomes in the group that was not exposed to the intervention and the experimental group. The average class value in the group exposed to the intervention was 39.45, while the average posttest value increased to 77.92. In contrast, the average class value in the group that was not exposed to the intervention was 41.58, with an increase to 44.50 in the posttest. Further descriptive analysis revealed a significant increase in the mean, median, and mode scores in the intervention group after treatment. The t-test showed a significance value of 0.000 (p < 0.05), which supports the hypothesis that the LKPD-assisted PjBL model has a significant effect on improving students' high-level thinking skills and learning outcomes.